Provision of special diets to children in public nurseries and kindergartens in Kraków (Poland) - Piórecka, Beata; Kozioł-Kozakowska, Agnieszka; Holko, Przemysław; Kowalska-Bobko, Iwona; Kawalec, Paweł (Frontiers in Nutrition, 2024)
Background: A specialized diet could be due to an allergy or other medical needs and also religious or cultural reasons. This study aimed to assess the availability and provision of special diets in kindergartens and nurseries financed by the Municipality of Kraków. Methods: This observational cross-sectional study was based on a diagnostic survey carried out using the Computer-Assisted Web Interview method and addressed to the managers of nurseries (n=21) and kindergartens (n=71) and, separately, to the parents of children attending these facilities (n=1096). Nonparametric tests were applied for an unadjusted comparison between children at nurseries and those at kindergartens. Results: Children with particular dietary requirements received special diet meals in 95.2% of nurseries and 60.5% of kindergartens. The availability of special diets was associated with the type of facility (p=0.001), the number of children who ate in the facility (p=0.032), and the daily cost of meals served to children (p=0.009). The cost of meals was higher in kindergartens that offered special diets vs those that did not offer such diets (p<0.001). According to parents, 96.4% of the total number of children ate meals served in the facilities. In nurseries, 16.1% of children were on a special diet (as per the doctor’s recommendations in 11.7% of cases and according to parents’ own choice in 4.4%). In kindergartens, a special diet was served to 12.7% of children (doctor’s recommendations, 8.5%; parents’ own choice, 4.2%). The most common reason for using a special diet was food allergy (8.2% of children in nurseries and 5.8% of children in kindergartens). It was reported more often by the parents of children attending nurseries than by the parents of children attending kindergartens (8.0% vs. 4.2%, p=0.007). The requirement for a special diet was found to be associated with the age of children (p<0.033) and the use of oral treatment for chronic disease (p<0.001). Conclusion: Providing special diets for children is better in nurseries than in kindergartens. Legal regulations are urgently needed to ensure equal access to adequate nutrition for all children with special dietary needs in childcare facilities.